Correlates of dietary energy misreporting among European adolescents: the Healthy Lifestyle in Europe by Nutrition in Adolescence (HELENA) study. Issue 8 (18th February 2016) - Bel-Serrat, Silvia; Julián-Almárcegui, Cristina; González-Gross, Marcela; Mouratidou, Theodora; Börnhorst, Claudia; Grammatikaki, Evangelia; Kersting, Mathilde; Cuenca-García, Magdalena; Gottrand, Frederic; Molnár, Dénes; Hallström, Lena; Dallongeville, Jean; et al.
Abstract: This study examined the correlates of dietary energy under-reporting (UR) and over-reporting (OV) in European adolescents. Two self-administered computerised 24-h dietary recalls and physical activity data using accelerometry were collected from 1512 adolescents aged 12·5–17·5 years from eight European countries. Objective measurements of height and weight were obtained. BMI was categorised according to Cole/International Obesity Task Force (IOTF) cut-off points. Diet-related attitudes were assessed via self-administered questionnaires. Reported energy intake (EI) was compared with predicted total energy expenditure to identify UR and OV using individual physical activity objective measures. Associations between misreporting and covariates were examined by multilevel logistic regression analyses. Among all, 33·3 % of the adolescents were UR and 15·6 % were OV when considering mean EI. Overweight (OR 3·25; 95 % CI 2·01, 5·27) and obese (OR 4·31; 95 % CI 1·92, 9·65) adolescents had higher odds for UR, whereas underweight individuals were more likely to over-report (OR 1·67; 95 % CI 1·01, 2·76). Being content with their own figures (OR 0·61; 95 % CI 0·41, 0·89) decreased the odds for UR, whereas frequently skipping breakfast (OR 2·14; 95 % CI 1·53, 2·99) was linked with higher odds for UR. Those being worried about gaining weight (OR 0·55; 95 % CI 0·33, 0·92) were less likely to OV. Weight status and psychosocial weight-related factors were found to be the major correlates of misreporting. Misreporting may reflect socially desirable answers and low ability to report own dietary intakes, but also may reflect real under-eating in an attempt to lose weight or real over-eating to reflect higher intakes due to growth spurts. Factors influencing misreporting should be identified in youths to clarify or better understand diet–disease associations.